Whole-genome association studies of distribution of developmental abnormalities and other breeding-valuable qualitative traits in offspring of the Russian large-white boars - A. A. Traspov; O. V. Kostyunina; A. A. Belous; T. V. Karpushkina; N. A. Svejenceva; N. A. Zinovieva (Вавиловский журнал генетики и селекции)
Identifying genome regions that are directly or indirectly associated with developmental defects and malformations in domesticated pigs can help identify genomic traits used as biomarkers of the structural and functional composition of the body, their metabolic status and genetic diseases as well. Such studies are directly related to the improvement of the economic efficiency, as they allow identification and exclusion of defect animals, who may carry target genes not appearing phenotypically, from the breeding process. In the current work, we have searched for these kind of target genes and genome regions with conducting the genome-wide association studies using PorcineSNP60K BeadChips (Illumina, San Diego, USA). A total of 48 boars of a large white breed of the nucleus farm “Znamenskoe” were analyzed for 21 traits of indicated shortcomings of the exterior and defects of development in 39,153 their offspring.  Calculations were made using a mixed type linear model in package GEMMA. In this study, we selected only 36,704 polymorphic SNPs from an initial 61,000-strong SNP set. After GWAS, we obtained 24 alleles in 11 corresponding genes  (P < 0.1) in the genome of pigs, which are significantly correlated with traits of developmental abnormalities such as anal atresia (ARMC7,FANCC,RND3,ENSSSCG00000017216), limb problems (PAWR,NTM,OPCML,ENSSSCG00000040250, ENSSSCG00000017018) and tremor of piglets (RIC3,ENSSSCG00000032665). Also, co-expression of the NTM,OPCMLand  RND3genes was revealed. This study confirms the relevance of using the single SNP detection according to the single trait approach in associative studies, even for small sample numbers.